ANALISIS KOMODITAS UNGGULAN PERKEBUNAN DAN PENGARUHNYA TERHADAP PENDAPATAN PETANI DI DESA TANAH MERAH KECAMATAN TANAH MERAH KABUPATEN INDRAGIRI HILIR - nandari, Ismi Rosyita; Syahza, Almasdi; Mujiono, Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the low price of coconut commodity. The purpose of this study is to determine how much influence the price of coconut has on the income of coconut farmers. The population in this study were farmers in Tanah Merah Village consisting of 100 farmers who selected samples using the Slovin formula so that they produced 50 samples. In collecting data, namely by interviewing and distributing questionnaires with research instruments. Furthermore, to analyze the data using the chi-square test. When viewed from the results of statistical analysis with the chi-square test, it can be seen that the Asymp. Sig. (2-sided) 0.027. This value is less than 0.05. So it can be concluded that there is an effect of the price of superior coconut plantation commodities on the income of farmers in Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency. it can be concluded that there is an effect of coconut commodity prices on farmers' income.Key Words: Coconut Prices, Chi-Square Test, Farmers' Income